Microbiota bacteriana em lagostas espinhosas de ocorrência no litoral cearense - Oliveira, Ana Vládila da Silva (2023)
In Brazil, the commercial capture of lobsters began in the 1950s and, currently, this marine fishing sector still has socioeconomic relevance, especially in coastal cities. This crustacean has an external market reaching significant values, which explains its role in the Brazilian trade balance. The literature regarding Brazilian spiny lobster populations tends to focus only on parameters linked to capture and life cycle, however, relevant aspects of lobster biology, such as the diseases to which they are exposed and their microbiota, have been less studied. There is no information about the natural microbiome of lobsters found on the Brazilian coast and the decline in lobster stocks has always been associated with the overexploitation of this resource. Therefore, the objective of this research was to quantify, evaluate, identify and characterize the bacterial microbiota (in the intestine, hepatopancreas and hemolymph) of spiny lobsters exploited by the Ceará fishing industry, in order to verify the occurrence of variations in the bacterial microbiota in the different anatomical strata of lobsters and between two species of this crustacean. For the development of the present study, collections were carried out in the community of Redonda beach, located in the municipality of Icapuí - Fortaleza/CE. Twenty individuals were collected, ten of them belonging to the species Panulirus argus and the rest belonging to the species Panulirus laevicauda. The animals were sacrificed and dissected to access the microbiota using conventional bacterial cultivation techniques. The bacterial isolates were subjected to morphological, biochemical and enzymatic characterization tests and subsequent identification using molecular biology techniques. The results demonstrated a quantitative difference in the cultivable bacterial groups of the lobster microbiota, with higher numbers recorded in green lobsters. The hemolymph was among the strata with the lowest abundance of bacteria. When comparing the total count of microorganisms in the lobsters studied, it was found that there was no significant difference in the abundance of Vibrio, showing that this genus had similar relative abundance in red and green lobsters. Of the total Cultivable Heterotrophic Bacteria (BHCs), 96.5% were Gram negative rods. When investigating biofilm production in BHCs, the hegemony of microorganisms with the capacity to produce exopolysaccharides (81%) was noticeable. Although the microbiota of both lobster species demonstrate the ability to hydrolyze proteases, it was observed that the microbiota of P. laevicauda lobsters has a higher prevalence of caseinase-producing bacteria in relation to P. argus. The genus Vibrio was ubiquitous in both species. Fifteen samples were genotypically identified at the genus level, showing the presence of the genera Bacillus, Enterobacter, Photobacterium, Pseudomonas, Shewanella and Vibrio. The cultivable bacterial microbiota of spiny lobsters found on the coast of Ceará, Panulirus argus (red lobster) and Panulirus laevicauda (green lobster), may differ in abundance and diversity. The genera Pseudomonas, Vibrio and Bacillus demonstrate biotechnological potential for probiotic use by expressing a diversity of digestive enzyme activities and exopolysaccharide production. This research presents for the first time results regarding the microbiome of different strata of the species Panulirus argus and Panulirus laevicauda, two species of lobsters of extreme ecological and economic importance for the coast of Ceará.